Low serum sphingolipids in children with attention deficit-hyperactivity disorder - Henríquez-Henríquez, Marcela P.; Solari, Sandra; Quiroga, Teresa; Kim, Benjamin I.; Deckelbaum, Richard J.; Worgall, Tilla S. (Frontiers in Neuroscience, 2015)
Background: Attention deficit-hyperactivity disorder (ADHD) is the most prevalent neuropsychiatric condition in childhood. ADHD is a multifactorial trait with a strong genetic component. One neurodevelopmental hypothesis is that ADHD is associated with a lag in brain maturation. Sphingolipids are essential for brain development and neuronal functioning, but their role in ADHD pathogenesis is unexplored. We hypothesized that serum sphingolipid levels distinguish ADHD patients from unaffected subjects. Methods: We characterized serum sphingolipid profiles of ADHD patients and two control groups: non-affected relatives and non-affected subjects without a family history of ADHD. Sphingolipids were measured by LC-MS/MS in 77 participants (28 ADHD patients, 28 related controls and 21 unrelated controls). ADHD diagnosis was based on the Diagnostic and Statistical Manual of Mental Disorders (DSM IV-TR). Diagnostic criteria were assessed by 2 independent observers. Groups were compared by parametrical statistics. Results: Serum sphingomyelins C16:0, C18:0, C18:1, C24:1, ceramide C24:0 and deoxy-ceramide C24:1 were significantly decreased in ADHD patients at 20-30% relative reductions. In our sample, decreased serum sphingomyelin levels distinguished ADHD patients with 79% sensitivity and 78% specificity. Conclusions: Our results showed lower levels of all major serum sphingomyelins in ADHD. These findings may reflect brain maturation and affect neuro-functional pathways characteristic for ADHD.